Effect of tree-spacing and integrated nutrient management on Triticum aestivum L. under poplar-based agroforestry system - ., Garima; Singh, Ranjeet; Kumari, Yourmila; Dubey, G.D. (Indian Journal of Agroforestry, 2019)
The study was conducted at experimental farm of Department of Silviculture and Agroforestry, Nauni, Solan, Himachal Pradesh in rabi season of 2015. The experiment was conducted in factorial randomized block design to analyse theimpact of Populus deltoides (poplar) tree spacing viz., S (4 m × 6 m) S (4 m × 4 m) and S (control i.e. without poplar), and six 1 , 2 3 fertilizer doses viz., T (recommended dose of fertilizers; RDF), T (farm yard manure; FYM on N equivalent ratio), T 1 2 3 (vermicompost on N equivalent ratio), T (75% FYM and 25% vermicompost on N equivalent ratio), T (50% FYM and 50% 4 5vermicompost on N equivalent ratio) and T (50% (25% FYM + 25% vermicompost) + 50% chemical fertilizers) on growth and 6 yield performance of Triticum aestivum (wheat) under poplar based agroforestry system. The T had shown better results in 6 the growth and yield of wheat than the other studied treatments. There was a 19.73 and 29.78% reduction in wheat yield in S 1and S , respectively as compared to open (control). The study revealed that tree spacing (S ) and integrated fertilizer doses 2 1 (T ) had a significant effect on growth and yield parameters of wheat.